1997
DOI: 10.1007/bf02880922
|View full text |Cite
|
Sign up to set email alerts
|

High-energy photoproduction

Abstract: The study of photoproduction reactions has gained a unique opportunity with the HERA data. The high center of mass energy allows to carry out quantitative tests of QCD, to explore the substructure of both the photon and the proton and to shed new light on soft and diffractive processes. In this report we review the HERA results, comparing them with the reach of fixed target photoproduction experiments and complementary measurements from e + e − and hadron colliders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 181 publications
1
9
0
Order By: Relevance
“…Using for B 0,pP ≈ 2.4GeV −2 and for α ′ P ≈ 0.25GeV −2 , as found in [38,39], one gets for LHC energies (s = (2 × 7TeV) 2 ,s 0 = 1GeV 2 ) b 0 ≈ 1 fm, which is small compared to the nuclear radius.…”
Section: General Survey Of Peripheral Collisionssupporting
confidence: 53%
See 2 more Smart Citations
“…Using for B 0,pP ≈ 2.4GeV −2 and for α ′ P ≈ 0.25GeV −2 , as found in [38,39], one gets for LHC energies (s = (2 × 7TeV) 2 ,s 0 = 1GeV 2 ) b 0 ≈ 1 fm, which is small compared to the nuclear radius.…”
Section: General Survey Of Peripheral Collisionssupporting
confidence: 53%
“…This is made possible by the large flux of quasi-real photons from the electron (positron) beam (for a review see [38]). The obtained γp center-of-mass energies (up to W γp ≈ 200 GeV) are an order of magnitude larger than those reached by fixed target experiments.…”
Section: γ-A Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…4(d) is that the cross section for this case does not include the direct component since our calculation are performed only to leading order. It is known, however, that in next-to-leading order the direct component presents appreciable contribution for x γ > 0.75 [26].…”
Section: Diffractive Jets and Zeus Datamentioning
confidence: 96%
“…Refs. [1]- [3]; a comprehensive earlier review on this subject can be found in Ref. [4]) as a unique testfield for diffraction, an interface between "soft" and "hard" physics, with three independent kinematical variables, the c.m.s energy W = √ s, the transferred momentum √ −t and the virtuality of the external particle(s) Q 2 = −q 2 involved simultaneously.…”
Section: Introductionmentioning
confidence: 99%